Legal Aspects of the Official Introduction of the Bill in the Majilis of the Parliament - ZHEKSEKIN, Almaz; BOZHKARAULY, Altai; BOTAGARIN, Ruslan; ABYLASIMOV, Murager; ZHUMASHEVA, Aigul (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018DO - 10.14505//jarle.v9.7(37).36, 2019)
In the course of the study, the prerequisite for this period is the period of legislative initiative. The stage of introduction of the bill is the implementation of the right of legislative initiative. The main subject of the legislative initiative is the Government of Kazakhstan, as it needs legal support for economic reform in the course of the reform process in the country and needs to choose the forms and methods of this regulation. The government justifies the adoption of the bill, its consequences and expected results. Right to introduce bills to the Majilis is one of the powers of the government (paragraph 3 of article 66 of the Constitution of Kazakhstan). Summing up, the government's right to introduce draft laws simultaneously means its obligation, since, first, by giving instructions on introducing the draft law to the Parliament; the President exercises legislative powers through the government.